PSYCHOLOGICAL AND PEDAGOGICAL COMPREHENSION OF "THINKING OF MILITARY HIGHER EDUCATIONAL INSTITUTION CADETS" - Kozhedub, O.; Gavryushenko, V.; Kalyshenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Scientific article authors, having analyzed separate aspects of philosophical, psychological and pedagogical literature, operationalize and find out comprehension of "thinking of military higher educational institution cadets". The article notes that social and psychological nature of thinking should be appropriately researched with activity based approach, because cognitive activity of military higher educational institution cadet is founded on thinking. Such an approach allows the authors to discover personal (the necessity of knowledge, significance of the acquired knowledge, the goals and plan of cognitive activity) and processional (analytical and synthetical activity) aspects of military higher educational institution cadets. In brief authors describe the following mental phenomena: mental activity (system of mental actions and operations aimed to definite goal achievement), mental operations (analysis, synthesis, generalization, classification and abstraction, etc.), types of thinking (analytical, critical, practical, economical, ecological, scientific, etc.), forms of thinking (concept, judgment, inference). The authors emphasize that understanding of social and psychological nature of thinking of military higher educational institution cadets will allow the military teacher to appropriately implement such modern pedagogical techniques as situational teaching (case-method), critical (emergency) situation technique, complete understanding technique, heuristic teaching technique, simulation technologies, etc. The final step is to determine the prospects of scientific research, which the authors see in the formation of certain types of thinking (for example, analytical, critical, professional, creative, etc.) of cadets by means of the modern pedagogical technologies.
Keywords: thinking, military higher educational institution cadet, thinking of military higher educational institution cadet